2014
DOI: 10.1155/2014/618943
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic, and Electrochemical Studies on Some New Copper(II) Complexes Containing 2-{[(Z)-Phenyl (Pyridine-2-yl) Methylidene] Amino}Benzenethiol and Monodentate Ligands

Abstract: Five new mononuclear copper(II) complexes, namely, [Cu(L)(ImH)]·ClO41; [Cu(L)(Me-ImH)]·ClO42; [Cu(L)(Et-ImH)]·ClO43; [Cu(L)(2-benz-ImH)]·ClO44; [Cu(L)(benz-ImH)]·ClO45, where HL = 2-{[(Z)-phenyl (pyridine-2-yl) methylidene] amino} benzenethiol; ImH = Imidazole; Me-ImH = Methy-limidazole; Et-ImH = Ethyl-imidazole; 2-benz-ImH = 2-methyl-benzimidazole; benz-ImH = benz-imidazole, have been synthesized and characterized by various physicochemical and spectroscopic techniques. Magnetic moments, electronic spectra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[23][24][25][26][27] Of these substituents, pyridine functionality not only acts as an efficient ligand, 24,28,29 but also facilitates a decrease in the copper reduction potential, resulting in the preferential reduction of the surface bound Cu(II) to Cu(I). [29][30][31][32][33][34][35] This coordinated Cu can then act as a catalyst for the deposition of further Cu(II) ions from solution, allowing controlled seeded growth by electroless deposition. 28,29,36 In the case of CNTs, we have reported that pyridine (py) functionalization may be achieved through 1,3-dicyclohexylcarbodiimide (DCC) coupling of isonicotinic acid (with CNT-OH groups) or 4-hydroxypyridine (with CNT-CO 2 H groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Of these substituents, pyridine functionality not only acts as an efficient ligand, 24,28,29 but also facilitates a decrease in the copper reduction potential, resulting in the preferential reduction of the surface bound Cu(II) to Cu(I). [29][30][31][32][33][34][35] This coordinated Cu can then act as a catalyst for the deposition of further Cu(II) ions from solution, allowing controlled seeded growth by electroless deposition. 28,29,36 In the case of CNTs, we have reported that pyridine (py) functionalization may be achieved through 1,3-dicyclohexylcarbodiimide (DCC) coupling of isonicotinic acid (with CNT-OH groups) or 4-hydroxypyridine (with CNT-CO 2 H groups).…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used approach to facilitate the deposition of Cu nanoparticles on CNTs is through oxidation of the CNTs to graft epoxide, hydroxyl, and carboxyl groups on the surface. We have also shown that functionalization with pyridine, phosphines, and thiols of CNTs can be achieved in a number of ways, and this allows for coordination of metal ions, compounds, or nanoparticles. Of these substituents, the pyridine functionality not only acts as an efficient ligand, ,, but also facilitates a decrease in the copper reduction potential, resulting in the preferential reduction of the surface-bound Cu­(II) to Cu­(I). This coordinated Cu can then act as a catalyst for the deposition of further Cu­(II) ions from solution, allowing controlled seeded growth by electroless deposition. ,, In the case of CNTs, we have reported that pyridine-(py-)­functionalization may be achieved through the 1,3-dicyclohexylcarbodiimide (DCC) coupling of isonicotinic acid (with CNT–OH groups) or 4-hydroxypyridine (with CNT–CO 2 H groups) …”
Section: Introductionmentioning
confidence: 99%
“…The high stability of the isonicotinate's pyridine Lewis base interaction with Cu 2+ ensures the coordination. 22 Based on analogy with other Cu 2+ complexes with pyridine-type ligands, 40,41 immobilization with isonicotinic acid ligands will reduce the reduction potential resulting in the preferential reduction of the surfacebound Cu 2+ to Cu 0 . This already-deposited copper can then act as a catalyst for the deposition of further Cu 2+ ions from the solution, allowing the deposition to proceed in an autocatalytic manner.…”
Section: Discussionmentioning
confidence: 99%